EFEKTIFITAS PENGELOLAAN PORTAL AKADEMIK DI UNIVERSITAS RIAU (Studi Kasus di Fakultas Ilmu Sosial dan Ilmu Politik) - Risa Nurwati; Tuti Khairani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
It can no longer be denied that the development of information technologyhas changed the way people around the world living in running day-to- dayactivities. The existence and role of information technology in the life sector hasunwittingly brought the world into a new era of globalization faster than originallyenvisaged. These developments have also been utilized in the realm of publicservice, one example is the implementation Academic Portal at the University ofRiau in order to provide fast service, transparent and inexpensive to students.Effectiveness is a situation that shows the level of success of managementactivities in achieving the goals set in advance. In other words, effectiveness is theextent to which organizations carry out the entire task or achieve substanrially allof the target.This study aimed to examine the effectiveness of management at theUniversity of Riau Academic Portal based benefits, achievement of objectives andresults obtained after the implementation Academic Porta. This research wasconducted at the Faculty of Social and Political Sciences, University of Riau.The method used in this research is descriptive method with qualitativedata analysis and data collection techniques through interviews, observation andstudy of literature . Who become informants in this study were students FISIPUR, Chief Manager and Employee Portal Academic Computer Center at UPTFisip UR and UR.From the research conducted, it was found that management at theUniversity of Riau Academic Portal is quite effective because the goals set havebeen achieved, and the presence of beneficial results.Keywords : Effectiveness,Management, Academic Portal.